Pengembangan Multimedia Google Earth Berbasis Virtual Mata Pelajaran Ski di Madrasah Tsanawiyah (MTs) - Refni Dayu; Jamal Mirdad; Nidya Fitri (Ideas Publishing, 2022)
Multimedia Development of Virtual-Based Google Earth Learning in SKI Subjects in MTs, The development of virtual-based google earth learning multimedia is an effort to visualize places / locations in three dimensions because lectures are insufficient in expressing material orally and using media have not varied used by teachers so that students are unable to understand the material about SKI subjects. This has an impact on one of the factors that make SKI subjects difficult to understand. The research aims to develop multimedia learning SKI (History of Islamic Culture) in Madrasah Tsanawiyah Negeri 1 Solok by using an interactive multimedia format in showing the places where the dawah trip of Prophet Muhaamad saw. in Makkah and to find out the validity of virtual-based google earth learning multimedia. The research methods used are research and development (development research) the ADDIE model developed by Dick and Carry (1) needs analysis; (2) design of the developed product; (3) expert validation and revision; (4) field trials. Instruments for collecting data in this study are interviews, observations, validation sheets. The multimedia that has been developed is then tested for validity by experts using Aikens V. Research results show that the results of virtual-based google earth multimedia validation are categorized as very valid (0.915). Based on the validation results, this virtual-based google earth multimedia is valid for use in ski learning the dawah material of the Prophet Muhammad saw in Makkah.